Sequential Treatment with Modified Atkins Diet and Low Glycemic Index Treatment for Drug-Resistant Epilepsy in Children - Mulyan, Aparna; Kaushik, Jaya Shankar; Dabla, Surekha (Neuropediatrics, 2024)
Objectives The present study was designed to study the efficacy of sequential dietary therapy with a modified Atkins diet (mAD) followed by low glycemic index treatment (LGIT) in treating drug-resistant epilepsy in children.Methods This interventional study was conducted from February 2021 to February 2022 among children aged 6 months to 5 years who had failed to respond to more than two conventional and correctly chosen antiseizure medications. The primary endpoint was the proportion of good responders, that is, children with more than 50% seizure reduction. Secondary outcome measures were the proportion of children with seizure freedom, > 90% seizure reduction, and the nature of parent-reported adverse events.Results A total of 45 children were recruited for the study, with 6 children being lost to follow-up at 12 weeks. At 12 weeks, 30 of 39 (76.9%) children were good responders with more than 50% seizure reduction. Of these 30 children, 11 (24.4%) had more than 90% seizure reduction, with 9 (20%) achieving complete spasm freedom. Constipation was the most common side effect of the diet among the enrolled subjects.Conclusion Clinicians can consider sequential dietary therapy with a mAD in the first month followed by LGIT in the next 2 months for treating children who could not tolerate mAD beyond 1 month.
Keywords: infantile spasms; Lennox–Gastaut syndrome; drug-resistant epilepsy; ketogenic diet